Pembuatan Buket Bunga Dengan Daun Mahkota Berbahan Bawang Bombay Making A Flower Bouquet With Crown Leaves Made From Onions - Kuswidyaningrum N.J; Irene Elda Puspita; Agus Susanti; Widiati Alifah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The development of science and technology encourages the culture of people realizing their sympathy using a bouquet of fresh, dried, or synthetic flowers. Culture is favored by the public because the flower bouquet can be adjusted to the cost of the customer. Synthetic flower bouquet innovation has aesthetic value and long shelf life, the author made a flower crown leaf product using onions. Research to determine the stages of manufacture, valid experimental results, and public acceptance of the product. Using the methods of observation, literature, experimentation, documentation, interviews, questionnaires, and qualitative descriptive data analysis. The product manufacturing stage in the form of preparation of material tools, onion drying, printing, and decorating flowers takes ± 7 days or 1 week. Product validation according to 3 flower arranging experts was declared valid with the characteristics of yellowish brown color, onion fiber pattern, no aroma, and has a smooth wavy texture. The average results of the public test on 61 respondents from the AKS Ibu Kartini Semarang agency showed that the public liked the product (score 2). So that the product is accepted by the community and has the potential to become an opportunity in entrepreneurship. It is better to innovate a substitute for epoxy resin as a preservative for flower crown leaves from onions. Because epoxy resin after drying has a weight that is not comfortable for a bouquet of flowers that are held for a long time such as a bridal ceremony.